Meeting the challenges of measuring outcomes of home care programs: The Australian Community Outcomes Measurement (ACCOM) tool. Issue 3 (2nd July 2020) - Cardona, Beatriz; Fine, Michael; Riley, Shaun
ABSTRACT: Measuring the impact of care delivered at home for frail older people is a complex task given many confounding variables that may impact on the ability of service providers to identify the direct impact of their programs on their clients' well-being and quality of life. The recent publication of the 2018 Wellness and Reablement Report Outcomes indicated that organizations lack formal processes to measure the impact of their programs on service users. There are therefore limited data exits on measuring outcomes and the performance of the ACCOM tool in the real world. Knowledge of a strong causal relationship between services provided and outcomes enables confidence in assuming the care provided was largely responsible for the outcome achieved. This paper will reflect on the experiences of one service provider in Brisbane, in implementing the Australian Community Care Outcomes Measurement (ACCOM) tool to measure and demonstrate the impact of their programs.